What still prevents to acknowledge a major role for pulmonary rehabilitation in COPD treatment? - Incorvaia, Cristoforo; Panella, Lorenzo; Caserta, Antonello; Pellicelli, Irene; Ridolo, Erminia (Acta Biomedica Atenei Parmensis, 2019)
Chronic obstructive pulmonary disease (COPD) is a major health issue, particularly in aging people. Despite an increasing availability of drugs to treat COPD, recent data indicate that an actual control of the disease is achieved in a minority of patients. This makes apparent that additional treatments of COPD should be taken into account, such as pulmonary rehabilitation (PR), which was introduced in the 1960s and has large evidence of clinical effectiveness. PR is a non-pharmacologic therapy based on a comprehensive, multidisciplinary, patient-centered intervention comprising exercise training, self-management education and psychosocial support. PR treated patients develop an increased exercise tolerance and quality of life, reduced dyspnea and anxiety, and are concerned by less hospital admissions for disease exacerbations. Notwithstanding, the use of PR in COPD patients is negligible, being globally estimated in 2-5%. Here we update the evidence in favor of PR and the actual need to consider it as a treatment to be considered for COPD patients with significant impairment in daily living activities.